Petrographic characterization of granitic aggregates. - Ramos, V. (2011)
Granitic rocks are widely used as aggregates for concrete in Portugal. Although this type of rock is known in some countries to be non-potentially reactive to alkalis, there are reported cases of alkali-silica reaction related to granitic aggregates. As defined by the Portuguese specification LNEC E 461, the petrographic analysis is the first to be carried out when aggregates of unknown performance need to be characterized. The characterization is based on the determination of the percentage of reactive forms of silica in order to classify the aggregate as innocuous or as potentially reactive, according to classes similar to those defined in RILEM AAR-1. This assessment is followed by the mortar bar test (ASTM C 1260 or RILEM AAR-2) when the aggregate is classified in Class II or III. The local experience is that some of the granitic aggregates classified as innocuous by RILEM AAR-2 show a field performance different from that predicted by the tests. Therefore, a research project is being carried out in which systematic concrete prism tests (RILEM AAR-3 and RILEM AAR-4.1) are used to validate the results obtained by petrography and to establish which laboratory test(s) is(are) the most accurate for the assessment of the alkali reactivity of granites. In the present work, the first results of the research are presented, aiming to contribute to the reformulation of the national specification and to establish a possible correlation among the results from different methods.